al-Ulama al-Indonesiun fi Dirasah al-Hadits al-Mu'ashirah - Ade Pahrudin (Al-Manar: Jurnal Kajian Alquran dan Hadis, 2021)
Ramadan is the ninth month of the Hijri month. A month in which the Qur’an was revealed, forgiveness and mercy, so there are many scholars throughout the Islamic world recently and in the past who are interested in this month. One of them is Indonesian Islamic scholar, Syaikh Taufiq Hakim. He wrote a book called "The Virtues of Ramadan". The author quoted in his book fifty hadiths on the merit of Ramadan. However, the author transmitted these hadiths without mentioning their source, chain of transmission, and authenticity of hadith. Therefore, this research was carried out to find out the truth about the sources of these hadiths and the degree of their validity. This research is focused on the first twenty-five hadiths from his book. This research aims to know the authenticity of the hadith mentioned in the book with two points: First, to verify the authenticity of the hadiths identified by numbers - that is, the first hadith to the twenty-fifth -which the author narrated. Second, track the location of the hadith and select proof of the hadith ruling. After the research, the researcher found twenty-five hadiths: five of them are authentic, nine of them are weak, four of them are fabricated, and seven of them have no basis.